If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 12) = x(x + 14) + 12 Reorder the terms: x(12 + x) = x(x + 14) + 12 (12 * x + x * x) = x(x + 14) + 12 (12x + x2) = x(x + 14) + 12 Reorder the terms: 12x + x2 = x(14 + x) + 12 12x + x2 = (14 * x + x * x) + 12 12x + x2 = (14x + x2) + 12 Reorder the terms: 12x + x2 = 12 + 14x + x2 Add '-1x2' to each side of the equation. 12x + x2 + -1x2 = 12 + 14x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 12x + 0 = 12 + 14x + x2 + -1x2 12x = 12 + 14x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 12x = 12 + 14x + 0 12x = 12 + 14x Solving 12x = 12 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 12x + -14x = 12 + 14x + -14x Combine like terms: 12x + -14x = -2x -2x = 12 + 14x + -14x Combine like terms: 14x + -14x = 0 -2x = 12 + 0 -2x = 12 Divide each side by '-2'. x = -6 Simplifying x = -6
| -4.55=-12.2+v | | 6(a-7)=3(4a+4) | | 10M*5P+6Q+3P= | | 12y-37y=17 | | 10M^5P+6Q+3P= | | 12x+8=13x-8 | | 15-t+8t=-3 | | y^4n+y^2n= | | 5(4+15)=5y-60 | | 8=(x-1.5)+(x+1.5)+(x+1) | | -5+5b-8b=-2b-1 | | 8d-4d-6d-8=2 | | (4)(-4)(2)= | | 7(x-1)=2x+28 | | 3x+4w=12 | | 2.5(6x-4)=10+4(1.5+0.5x) | | w=10+-7t | | x^2y^4-x^2y-4x^2= | | 3x^2+3=-6x | | w=-7t+10t=3 | | 12x+2y=60 | | sqrtx=5 | | (5-1i)+(3+5i)= | | 3x+3+4x-1+x+2=180 | | 14+2x-2x-3=43 | | 2ahxb= | | hxa= | | 4(12-8)= | | 2x+x+x-4=180 | | 5x+9=79 | | x(21+x*x-10x)-26=0 | | a^2*2=16 |